PENGARUH METODE MENGAJAR GURU TERHADAP PRESTASI BELAJAR BAHASA ARAB SISWA SMP UNISMUH MAKASSAR - Rita Wati Ishak; Abd. Rahim Razaq (Universitas Muhammadiyah Makassar, 2018)
Junior High school Muhammadiyah of Makassar is an educational institution under the Muhammadiyah Primary and Secondary Education Council which always tries to motivate students to learn. Teachers in Junior High school Muhammadiyah of Makassarhave a duty and role to be able to improve student learning motivation. Teachers are required to have and master techniques and strategies that can stimulate students in learning, especially Arabic subjects. Therefore, this study tries to explore the effect of teacher teaching methods on the learning achievement of Arabic students atJunior High school Muhammadiyah of Makassar. The research method used is descriptive qualitative research by observation, interviews, documentation, and questionnaires as data collection techniques, data analysis techniques use a simple percentage formula. The student population is 76 people with a total sample of 35% of the total population of 35 students. The results of this study indicate the effect of teacher teaching methods on learning achievement of Arabic students atJunior High school Muhammadiyah of Makassar has been effective, this can be seen from the results of questionnaire calculations that students who feel very happy there are 9 students or 25.71%, who love 24 students or 68, 57%, less happy 2 students or 5.71% and not happy as much as 0%.Keywords: Influence, method, learning achievement